Transforming the Character of Indonesian Adolescent: a Positive Impacts of The Institutional Culture of High School Equivalency Programs - Rosmilawati, Ila; Sasmita, Karta (Journal of Nonformal Education, 2020)
Every adolescent in Equivalency Programs is unique, affected by interrelated factors of exclusion, such as school exclusion, family situation, poverty, social status and gender bias, and geographical location. Hence, Indonesia Equivalency Programs can target these particular groups to create responsible future citizens and develop human capabilities. This paper aims to explore the features of institutional culture of High School Equivalency Programs that impact on student’s character and learning performance. Ethnography study has been conducted in five nonformal schools in Banten Province that involved twenty five students in individual interviews. The results show that institutional culture of High School Equivalency Programs provides an opportunity for adolescent who engage in learning to transform their personal character to become more resilient, autonomous, sensing a positive identity and moral integrity. Conducive school culture build a positive image and sense of belonging of students in Equivalency Programs. In long term, this character will diminish destructive behaviour of young people and create active citizents. The positive impacts of institutional culture of High School Equivalency Programs on adolescent could potentially lead to higher social productivity and thus create greater economic growth.